ANALISIS PENGARUH PROFIL RISIKO DAN RENTABILITAS TERHADAP PERMODALAN SERTA DAMPAKNYA PADA KINERJA BPR KONVENSIONAL DI PROVINSI BANTEN PERIODE 2014 – 2018 - Lena Erdawati; Atik Atikah; Yanthi Meitri Gunawan (JMB : Jurnal Manajemen dan Bisnis, 2020)
The purpose of this study was to determine the effect of the Risk Profile and Profitability on Capital and its impact on BPR Performance in Banten Province. This research data uses secondary data published by the Financial Services Authority (OJK) for the 2014-2018 period, namely the financial statements of 15 BPRs domiciled in Banten Province with the criteria of having total assets above 30 billion. The indicators of this research are the Risk Profile which is proxied by: Non Performing Loans, Loan to Deposit Ratio, Cash Ratio, and Earning Asset Quality, Profitability Indicators which are proxied by Operational Costs, Operational Income, Capital Indicators which are proxied by Capital Adequacy Ratio and Rural Bank Performance Indicators. which is proxied by Return On Asset. The method used is a quantitative method. The data analysis technique used a panel data regression model, and hypothesis testing with the Eviews program and continued with path analysis. The results showed that partially CR has a significant effect on CAR while NPL, LDR, KAP and BOPO have no significant effect on CAR. Simultaneously, NPL, LDR, CR, KAP and BOPO have a significant effect on CAR. Partially NPL, KAP and BOPO have a significant effect on ROA while LDR, CR and CAR have no significant effect on ROA, simultaneously NPL, LDR, CR, KAP, BOPO and CAR have a significant effect on ROA.